THE DEFINITIONS OF INFORMATION WARFARE IN UKRAINIAN HISTORIOGRAPHY (Південний архів (історичні науки), 2023)
The article is an analysis of how the concept of “information warfare” is used by researchers from independent Ukraine. The purpose of the study is to examine the works of authors in independent Ukraine on the subject of the use of the concept of “information warfare”, in order to clarify the typical characteristics of this concept in the Ukrainian academic discourse and the presence or absence of a discussion about information warfare on the topic of history. Research methods are based on comparative analysis, comparing phenomena vertically (chronological changes in the interpretations) and horizontally (differences between the fields of study). The results of the study. Various trends in the coverage of information warfare were revealed in the works of researchers of military affairs, law, political science, and history. Namely, the approach of the former is apparently based on “classic” American definitions, recognizing both the technical and the propaganda component of information warfare, examining the psychological effect of both aspects. In the works of political scientists, attention was mostly paid to the propaganda component and its consequences, which, quoting O. Syshchuk, lead to the “informational-psychological hybrid war”. Historians also adhere to the study of the humanitarian component of the information confrontation, while going beyond the “information age” and using methods of information research to analyze the events of previous decades and even centuries, such as the struggle of the Nazi and Bolshevik totalitarian regimes, or the survival and competition of newspapers under the totalitarian system, which attempted to exercise full control over information in the country. Additionally, the works of the contemporary Ukrainian students are of interest, as the authors of which focus on a relevant and modern topic from their point of view: the Moscow invasion of Ukraine since 2014, trying to identify attempts to distort the history of Ukraine in the mass media of the aggressor state, and also looking at the Moscow-Ukrainian confrontation in a historical retrospective. Conclusions: 1) only some Ukrainian authors tried to provide a specific definition of “information warfare” even in works that put the issue in the title; 2) most researchers of various fields acknowledged or used the main components of the theory of information warfare proposed by American authors; 3) the concept was used to describe historical events beyond the realities of the 21st century.
Keywords: information war, information warfare, information operations, historiography, cyberwar, psychological operations